Fuel Consumption Losses and Traffic Performance as a Consequence of Universitas Islam Indonesia Faculty of Law Building at Simpang Pamungkas, Kaliurang, Yogyakarta - Laziqoh Zahatul Tolab; Miftahul Fauziah (Rekayasa Sipil, 2026)
This study analyzes the impact of traffic performance at Pamungkas Intersection, Kaliurang, Yogyakarta, after the relocation of the Faculty of Law of Universitas Islam Indonesia to the Integrated Campus. The relocation has significantly increased traffic volume, resulting in congestion and a decline in intersection performance. This study aims to assess current traffic conditions, forecast future scenarios, and propose effective alternative solutions to enhance traffic flow. Additionally, to determine the fuel consumption and operational costs of the vehicle. The methodology employed was a descriptive, quantitative approach, utilizing both primary and secondary data collection. Primary data included intersection geometry conditions, vehicle volume, and queue length, while secondary data included the population of Sleman Regency. The analysis is based on PKJI 2023, and the level of service is based on PM No. 96 of 2015. The results showed that the intersection currently operates at a Level of Service (LOS) of F, with a degree of saturation exceeding 0.85. Two alternative improvement scenarios were proposed: (1) signal redesign and reduction of side barriers, and (2) the same with road widening. Although both alternatives reduce the degree of saturation, Alternative 2 exhibits relatively better performance, while still maintaining LOS F. In terms of environmental impact, Alternative 2 results in lower fuel consumption and thus reduced emissions. The highest vehicle operating cost is recorded for medium passenger cars (MP) at IDR 14,869.86/km, followed by motorcycles (MC) and medium-sized vehicles (KS).